2022
DOI: 10.3390/ijerph192113792
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Ketamine Infusion after Suicide Attempt: New Frontiers in Treating Acute Suicidality in a Real-World Medical Setting

Abstract: Ketamine, in research settings, rapidly reduces suicidal thoughts 2–24 h after a single infusion in patients with high suicidal ideation. In this study, the authors investigate ketamine’s effects on suicidality in a real-world sample of recent suicide attempters on a tertiary-care Consultation-Liaison (CL) psychiatry service. Using an open-label design, 16 transdiagnostic CL patients were recruited, 18–65 years old, to receive a single dose of intravenous ketamine (0.5 mg/kg) in the acute medical setting. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 76 publications
0
0
0
Order By: Relevance
“…Improvement was contained through the full length of the third infusion and follow-up after the sixth and 12 th weeks. Many similar earlier studies, including a meta-analysis, corroborate the result that continual sub-anesthetic ketamine infusions significantly and consistently reduce suicide ideation [84,85]. Shivanekar et al reported that ketamine quickly decreases suicidal thinking by 2-24 hours after a single infusion among patients with intense suicidal thought processes [86].…”
Section: Discussionmentioning
confidence: 65%
“…Improvement was contained through the full length of the third infusion and follow-up after the sixth and 12 th weeks. Many similar earlier studies, including a meta-analysis, corroborate the result that continual sub-anesthetic ketamine infusions significantly and consistently reduce suicide ideation [84,85]. Shivanekar et al reported that ketamine quickly decreases suicidal thinking by 2-24 hours after a single infusion among patients with intense suicidal thought processes [86].…”
Section: Discussionmentioning
confidence: 65%